Experienscape: expanding the concept of servicescape with a multi-stakeholder and multi-disciplinary approach (invited paper for 'luminaries' special issue of International Journal of Hospitality Management). (January 2019) - Pizam, Abraham; Tasci, Asli D.A.
Abstract: Since Bitner's (1992) introduction of the servicescape concept, many conceptual and empirical studies have been conducted. Even though a relatively solid theoretical base has been established, the nature of the concept has not been updated with contemporary views on theories explaining behavior of consumers, employees and other stakeholders. Hence, the current study scanned the literature on servicescape and relevant concepts in order to update servicescape. The review of literature resulted in a new term, experienscape that is enhanced with the organizational culture of hospitality and the inclusion of employees, as both internal customers and service providers, as well as other stakeholders. For a comprehensive understanding of experienscape, a multidisciplinary approach is proposed by integrating views and theories from marketing, human resource management, organizational behavior, psychology, social psychology, communication, architecture, environmental design, and other related fields.